Gejala Depresi pada Lanjut Usia di Masa Pandemi Covid-19 - Made Dian Shanti Kusuma; Anak Agung Ayu Yuliati Darmini (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Corona Virus Diseases (Covid-19) 's impact on older adults leads to physical health problems and can affect psychological issues such as depressive symptoms. This study aims: To determine the prevalence of depressive symptoms in older adults and the related factors that influence depressive symptoms. Methods: This study uses a literature review approach based on data sources from Google scholar, PubMed, and ProQuest.Then, 17,323 articles were filtered based on inclusion criteria, and 14 were included in this study. Results: The prevalence of depressive symptoms ranged from 7.7% to 62.3%. The older adults at risk of having symptoms of depression are the older adults in older age groups ≥ 75 old age, living alone, loneliness, lack of social contact with family and friends, and older adults with comorbidities or illnesses. The prevalence of depressive symptoms among older adults with comorbidities was 61%. Conclusion: The results of this literature study can be used as a basis for providing interventions to older adults at risk of having symptoms of depression so that older adults can achieve physical and psychological well-being.